Efektivitas Bimbingan Konseling Anak Remaja di GPDI Elshadai Cepiring - Tirza Nadia; Fianus Tandiongan; David Priyo; Elesabet Elesabet (STT Kristus Alfa Omega, 2022)
Effectiveness is a measurement of the success or failure of an organization to achieve its goals. If an organization succeeds in its objectives, then the organization has been running effectively. GPDI Elshadai Church in Cepiring. Based on the results of interviews and the analysis conducted by the researcher, it is known that the counseling guidance for adolescents at GPDI Elshadai Cepiring church is less effective, this can be seen from most respondents who do not understand the aims of holding counseling guidance in the church and most are less active in participating the counseling guidance program.